Differences in Generation Y male and female customers’ perceived mobile banking trust, information, and system quality - Marko van Deventer (Banks and Bank Systems, 2024)
Trust is key to mobile banking adoption, shaping customer confidence in the service. Trusting behaviors and expectations vary between genders and across generational cohorts, influenced by factors like system and information quality. As such, the purpose of this study was to determine whether South African Generation Y male and female banking customers differ in their mobile banking trust, system, and information quality. In accordance with a descriptive research design, self-administered surveys were voluntarily distributed to 334 South African mobile banking participants. Using structural equation modeling, the study found that, among the male participants, the system quality of mobile banking predicts their mobile banking trust (β = 0.72, p < .001) and perceived information quality of the system (β = 0.94, p < .001). However, their mobile banking trust had an insignificant influence on their perceived information quality (β = –0.04, p > .001). For female Generation Y banking customers, mobile banking system quality was a significant predictor of both trust (β = 0.53, p < .001) and information quality (β = 0.69, p < .001). In addition, the path between trust and information quality was statistically significant (β = 0.17, p < .05). Determining the role of trust and its relationship between information and system quality of mobile banking among males and females is essential for understanding customer behavior, enhancing user experience, mitigating perceived risk, and guiding strategic decision-making in the mobile banking industry.